Prevalence of Different Types of Enteritis in Camels of Rajasthan - Asopa, Shesh; Vyas, Indu; Joshi, Ashish; Arora, Rajni; Dadhich, Hemant (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
For the present study, a total 80 tissue specimens of intestinal tract were examined from carcasses of camel, irrespective of sex, age  groups and breeds, from July 2017 to June 2018. Out of these, 32 samples representative of gross lesions were processed for subsequent  histopathological examination. An overall incidence of enteritis in camel was recorded as 40 % (32/80). The occurrence of various types  of enteritis, i.e., catarrhal enteritis, necrotic enteritis, necro-haemorrhagic enteritis, eosinophilic enteritis and haemorrhagic enteritis were 15.00, 6.25, 6.25, 5.00 and 7.50 %, respectively. Catarrhal enteritis was the most prevalent and eosinophilic enteritis least prevalent  conditions affecting intestines of camels in Rajasthan during the study period.
Keywords: Camel; Enteritis; Intestine; Rajasthan